Optimizing Patient Appointment Scheduling in Neurology Clin-ics Using Agile-Based Appointment Management System - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
Patient appointment management is a critical aspect of neurology clinic operations, especially given the complexity of patient care and the increasing number of patients requiring specialized attention. Capacity and efficiency challenges in scheduling negatively impact patient waiting times and optimal access to care. This research adopts an Agile approach in developing an information technology-based appointment management system to address scheduling issues in neurology clinics. The research methods include a literature study, interviews with relevant parties, patient surveys, system prototype development, and end-user evaluation. The implementation of the Agile-based appointment management system resulted in a significant reduction in patient waiting time and increased patient satisfaction. Data analysis showed that the use of information technology in scheduling improved the efficiency of using clinic resources and minimized the risk of delays in diagnosis and treatment. This study contributes to developing an adaptive and effective appointment management system in neurology clinics. It provides a foundation for developing better systems to improve healthcare quality and patient satisfaction in the long term.